Biostratigraphy of the upper Bajocian-middle Callovian (Middle Jurassic), South America - Riccardi, Alberto Carlos (1991)
The biostratigraphic division of the upper Bajocian-middle Callovian of South America is based on ammonites from different sections of the following provinces and regions: Neuquén, Mendoza, and San Juan in Argentina; Malleco, Linares, Talca, Atacama, Antofagasta, and Tarapacá in Chile. The complete upper Bajocian-middle Callovian succession includes the following biostratigraphic units: the Megasphaeroceras magnum assemblage zone, lowermost upper Bajocian; the Cadomites-Tulitidae mixed assemblage, (?lower) middle and upper Bathonian; the Steinmanni zone, index Lilloettia steinmanni (Spath), uppermost Bathonian, with two local horizons — Stehnocephalites gerthi horizon (Argentina) and Choffatia jupiter horizon (northern Chile); the Vergarensis zone, index Eur y cep halites vergarensis (Burck.), near the Bathonian-Callovian boundary; the Bodenbenderi zone, index Neuquenicerás (Frickites) bodenbenderi (Tornq.), lower Callovian; the Proximum zone, index Hecticoceras proximum Elmi, uppermost lower Callovian; and the Rehmannia (Loczyceras) patagoniensis horizon, middle Callovian.